Acting performance in children's theater performances (Journal of the College of Basic Education, 2022)
The research is concerned with studying the work of the acting performance, which constitutes the importance of the acting performance in the children’s theater performances, as it constitutes an important factor in the interpretation of the dramatic events, through which a clear vision of the content of the show is achieved as well as excitement and entertainment. The research: as it benefits college and institute students, researchers, and workers in the field of children’s theater, and the aim of the research was: to identify the role of acting performance in children’s theater performances, this is in (the first chapter), while the second chapter (the theoretical framework) included two sections, the first topic : Dealing with the characteristics of the child’s theater between text and presentation, as for the second topic: the actor and techniques of representational performance in the child’s theater, down to the indicators, and in the third chapter, the research procedures were included, the researcher analyzed the research sample, used the descriptive analytical approach in dealing with the research community, and included ( Chapter IV) the results of the research and its discussion, the researcher reached the role of the act of acting performance in the performances of the child’s theater, which is achieved in communicating the idea of the presentation (form and content) through the actor’s expressive tools in emulation, simulation and play, and the researcher recommended the need to pay attention With acting performance and theatrical elements in presenting what is the best exciting and attractive in children's theater performances, the research is concluded with annexes, sources and references, as well as a summary of the research in English